Pengaruh Model Pembelajaran Jigsaw untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PAI di SD Pratama - Afrona Nurlaely; Alghazal, Sobar (UNISBA Press, 2024)
Abstract. This research aims to determine the effect of learning motivation using the jigsaw learning model in PAI subjects in grade 4 elementary school. The research objectives are: (1) to find out how students' learning motivation is before using the jigsaw learning model in PAI subjects (2) to find out how students' learning motivation is after using the jigsaw learning model in PAI subjects, (3) to find out how much influence the model has jigsaw learning in increasing learning motivation in PAI subjects. The research method used is a quasi-experimental method with a non-equivalent control group design. The subjects of this study were grade 4 students who used the jigsaw learning model. Data analysis technique using paired sample t test. The research results show that: (1) Motivation before using the jigsaw learning model can be seen from the average (mean) of the experimental class of 54.31 and the control class of 53.69. (2) Students' learning motivation after using the jigsaw learning model can be seen from the average (mean) in the experimental class which increased by 60.31 compared to the control class which was 53.81. (3) It can be seen from the SPSS output. It is known that the 2-tailed significance is 0.001 because the significance is <0.05 then H0 is rejected and H1 is accepted, also seen from tcount 7.931 > ttable 2.131 then H0 is rejected and H1 is accepted. So it can be concluded that there is a difference in motivation before and after treatment using the jigsaw learning model, and looking at the average (mean) it can be seen that the average after is 60.31 higher than before using the jigsaw learning model 54.31. The jigsaw learning model has proven effective in increasing student learning motivation in elementary schools. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi belajar dengan menggunakan model pembelajaran jigsaw pada mata pelajaran PAI di kelas 4 SD. Dengan tujuan penelitian yaitu: (1) untuk mengetahui bagaimana motivasi belajar siswa sebelum menggunakan model pembelajaran jigsaw pada mata pelajaran PAI (2) untuk mengetahui bagaimana motivasi belajar siswa sesudah menggunakan model pembelajaran jigsaw pada mata pelajaran PAI, (3) untuk mengetahui seberapa pengaruh model pembelajaran jigsaw dalam meningkatkan motivasi belajar pada mata pelajaran PAI. Metode penelitian yang digunakan adalah metode eksperimen semu dengan rancangan non-equivalent control group design. Subyek penelitian ini adalah siswa kelas 4 yang menggunakan model pembelajaran jigsaw. Teknik analisis data menggunakan uji t sampel berpasangan. Hasil penelitian menunjukkan bahwa: (1) Motivasi sebelum menggunakan model pembelajaran jigsaw dapat dilihat dari rata-rata (mean) kelas eksperimen sebesar 54,31 dan kelas kontrol sebesar 53,69. (2) Motivasi belajar siswa setelah menggunakan model pembelajaran jigsaw dilihat dari rata-rata (mean) pada kelas eksperimen menjadi meningkat sebesar 60,31 dibanding kelas kontrol sebesar 53,81.(3) Dapat dilihat dari keluaran SPSS. diketahui signifikansi 2-tailed sebesar 0,001 karena signifikansinya < 0,05 maka H0 ditolak dan H1 diterima, juga dilihat dari thitung 7,931 > ttabel 2,131 maka H0 ditolak dan H1 diterima. Sehingga dapat disimpulkan bahwa terdapat perbedaan motivasi sebelum dan sesudah perlakuan menggunakan model pembelajaran jigsaw, dan dilihat dari rata-rata (mean) terlihat bahwa rata-rata sesudahnya 60,31 lebih tinggi dari sebelum menggunakan model pembelajaran jigsaw 54,31. Model pembelajaran jigsaw terbukti efektif dalam meningkatkan motivasi belajar siswa di Sekolah Dasar